GAMBARAN PENGETAHUAN MAHASISWA FAKULTAS KEDOKTERAN GIGI TENTANG PENULISAN RESEP - K. Kiswaluyo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
Recipe is the final embodiment of competence, knowledge and expertise of clinicians in applying his knowledge in the field of pharmacology and therapeutics. Factors determining the selection of patients who used the drug dosage form. In the pediatric patients given the drug orally in liquid dosage forms of solusio, suspensions or emulsions, and solid dosage forms pulveres form (powder). The research aims to find a picture of student knowledge of dental school at the profession on how to write prescriptions in the form of powder.The results showed that more than 90% of professional degree students do not know how to write a prescription correctly.